2019
DOI: 10.1515/pac-2018-0802
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of ferrocenyl chalcones: synthetic scaffolds toward biomedical and materials science applications

Abstract: Ferrocene and its derivatives constitute versatile and interesting scaffolds for the global chemical enterprise due to its multiple applications that range from biomedical to materials science. Ferrocenyl derivatives are the leading compounds in our research for the syntheses and characterization as well as their potential biological applications. Among them, our recent focus has been in ferrocenyl chalcones as a framework for further derivatization. The proposed modifications consist on the incorporation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…The FT-IR/ATR spectra of all synthesized compounds were recorded in the wavelength range 400-4000 cm -1 using a Thermo ScientificNicolet iS10 apparatus. 1 H and 13 C NMR spectra of compounds 1 ̶ 3 were recorded on a Bruker Ascend 400 apparatus at room temperature in deuterated chloroform (CDCl3), while spectra of compounds 4 and 5 were recorded in deuterated dimethyl sulfoxide (DMSO-d6). All melting points were determined on Electrothermal apparatus.…”
Section: Methods For the Characterization Of The Synthesized Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FT-IR/ATR spectra of all synthesized compounds were recorded in the wavelength range 400-4000 cm -1 using a Thermo ScientificNicolet iS10 apparatus. 1 H and 13 C NMR spectra of compounds 1 ̶ 3 were recorded on a Bruker Ascend 400 apparatus at room temperature in deuterated chloroform (CDCl3), while spectra of compounds 4 and 5 were recorded in deuterated dimethyl sulfoxide (DMSO-d6). All melting points were determined on Electrothermal apparatus.…”
Section: Methods For the Characterization Of The Synthesized Compoundsmentioning
confidence: 99%
“…Singh et al demonstrated that ferrocene appended chalcone linked triazole allied organosilatranes possess high radical scavenging efficacy [9]. Moreover, other potential applications of investigated derivatives include molecular materials, redox-sensors, and polymers [1]. Our goal in this paper is to highlight the synthesis and antioxidant activity of ferrocenyl chalcones (Scheme 1) with particular prominence to the most active derivatives which represent an interesting starting point for the synthesis of some new pharmacologically active compounds.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A novel strategy based on multifunctional hybrids of ferrocene was then considered. This approach has recently been the subject of a large number of reviews [5][6][7][8][9][10][11][12][13][14][15][16] and the results have proved to be, to say the least, mixed. Nonetheless the redox motif [ferrocenyl-ene-phenol] remains the most biologically promising candidate to date, since compounds presenting this motif show remarkable antitumor properties both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of bio‐organometallic chemistry, the ferrocifen system continues to attract significant attention . These molecules possess a ferrocenyl‐ene‐ p ‐phenol motif, and a basic dimethylaminoalkoxy chain, as in 3 .…”
Section: Introductionmentioning
confidence: 99%